Konflik Ekonomi Amerika Serikat-China Setelah Perang Dagang - Dano, Dimasti (Jurnal Syntax Fusion, 2022)
The Research entitled: After the Trade War, Could the US-China Economic Conflict Will Continue? This is research with a descriptive qualitative approach. research that aims to understand the phenomena experienced by research subjects. This study aims to analyze the influence of the United States-China conflict as a result of Nanci Pelosi's visit to the economic relations of the two countries after the trade war conflict when the United States was led by President Trump in 2018. The study was conducted from 1 to 31 August 2022. Data collection techniques were conducted through studies literature related to research, including journals, news in newspapers, and others. The opportunity for the United States-China economic conflict is just a matter of time. One of them is through China's efforts to "reunify" Taiwan, as President Xi discoursed in 2021 by saying that reunification is a historical mandate and must be fulfilled. China has a military that is superior to Taiwan because, in addition to carrying out contingency actions against Taiwan, it also to faces the United States military in the Indo-Pacific. The United States will seek to support politically, militarily, and economically democratic Taiwan. Economic support is carried out through economic sanctions, such as those imposed by the United States on Russia or during a trade war conflict with China.